2008
DOI: 10.1093/eurheartj/ehn337
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of regional myocardial blood flow and function and reduction of infarct size with ivabradine: protection beyond heart rate reduction

Abstract: Ivabradine's protection goes beyond heart rate reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 31 publications
2
69
1
1
Order By: Relevance
“…In another study, where pigs were given ivabradine prior to revascularization, the authors found that ivabradine improved blood flow independent of heart rate. However the ivabradine was given intravenously in a high dose (0.6 mg/kg) compared to our study, where the patients per orally received 5 mg the evening before and 5 mg prior to the scan [30]. Above studies have taken into consideration that the difference in blood flow between T1DM patients and controls seems to be explained not only by the difference of receiving ivabradine or metoprolol.…”
Section: Limitationsmentioning
confidence: 73%
“…In another study, where pigs were given ivabradine prior to revascularization, the authors found that ivabradine improved blood flow independent of heart rate. However the ivabradine was given intravenously in a high dose (0.6 mg/kg) compared to our study, where the patients per orally received 5 mg the evening before and 5 mg prior to the scan [30]. Above studies have taken into consideration that the difference in blood flow between T1DM patients and controls seems to be explained not only by the difference of receiving ivabradine or metoprolol.…”
Section: Limitationsmentioning
confidence: 73%
“…It has been widely suggested that ß-blockers lessen the magnitude of the MI by decreasing oxygen consumption secondary to slow heart rate during or early after MI [108]. However, in a porcine model of AMI, the reduction in MI size granted by the administration of metoprolol before reperfusion was independent of the heart rate and blood pressure drop achieved during the MI induction [125], something that has been also demonstrated with the bradycardic agent ivabradine by Heusch and colleagues [126]. We have recently observed that the administration of metoprolol during ongoing ischemia resulted in a significant increase in myocardial salvage in comparison with its oral administration initiated few hours after reperfusion.…”
Section: Hyperoxygenation Of the Myocardiummentioning
confidence: 98%
“…Reduction of heart rate during stress or exercise by ß-adrenoceptor blockade or more selective bradycardic agents reverses the above unfavourable blood flow redistribution and attenuates myocardial ischemia [10][11][12]. Dronedarone also reduces heart rate at sinus rhythm [13,14] and the ventricular rate during atrial fibrillation [14,15].…”
Section: Dronedarone In Myocardial Ischemia/reperfusionmentioning
confidence: 99%
“…Modified from [5,7,8] [ 35,36] at increased density following myocardial infarction [37]. Although I f -channels contribute to cardiomyocyte calcium influx [38] which is increased during myocardial infarction and blocked by ivabradine [37], we currently do not know whether or not inhibition of I f channel activity underlies the benefit from ivabradine [12,39]. Dronedarone also inhibits the sodium-calcium exchange in cardiomyocytes [2], and the inhibition of sodium-calcium exchange by other agents attenuates cardiomyocyte calcium overload and hypercontracture and reduces infarct size [40].…”
Section: Dronedarone In Myocardial Ischemia/reperfusionmentioning
confidence: 99%